An integrated service solution for digital discount coupons processing - Araújo, J.
This paper describes a digital coupons management system that aims to dematerialize the couponing process since its origin (the Issuer) to its final state (the Consumer), passing by the Retailer of the product, and allowing to reduce costs, prevent frauds, improve the procedural efficiency and get knowledge about patterns of usage of coupons by consumer profiles. The system provides quality control of dematerialized coupons and Consumers mobile access, allowing the connection and integration with the information systems of Issuers and Retailers, which makes it an innovative system with a high degree of portability of its components. © Springer International Publishing Switzerland 2015.